Teknik pemijahan ikan Gabus (Channa striata) di Instalasi Budidaya Ikan Lahan Gambut Desa Garung Pulang Pisau - Tania Serezova Augusta; Rello Pernando (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
This study discusses the technique of spawning Snakehead fish (Channa striata) from the pre-spawning process to post-spawning in peatland media. The research was carried out in the Peatland Fish Farming, Garung Village, Jabiren Raya District, Pulang Pisau district. The research method used uses an observation method that is supported by primary and secondary data. Primary data obtained direct observation such as interviews with fish farmers and activities directly in the field, while secondary data obtained from data or information obtained directly from the source in the form of information and references that support research on Snakehead fish spawning. The type of pond used for spawning is a fiber tub pond with a size of 1x1x1 m3 and a diameter of 50 cm and a height of 70 cm, with a water level of 30 cm. The number of fish sampled was 14 by dividing each of the 7 female and male sires. The stages of spawning Snakehead fish begin with media preparation, parent preparation, parent selection, adaptation, maintenance, injection and spawning of Snakehead fish. The total number of fertilized eggs from the artificial spawning process was as much as 12,860 eggs with a mortality rate of 11% or the final yield after hatching was around 11,527 fish larvae. Keywords : Spawning, snakehead fish, injection